State promoting infrastructural maintenance of energy-saving enterprises civil construction - Doroshenko, V. (Ways to Improve Construction Efficiency, 2015)
The paper studies the problem of infrastructural maintenance of energy-saving enterprises civil construction. The directions of the state support the implementation of infrastructural maintenance of energy-saving enterprises civil construction, providing for consideration of structural components: personnel, information and consulting, financial, economic, legal and regulatory.